The role of brush cytology in diagnosing lesions of biliary tract - Sridevi, S.; Lakshmi, A. Bhagya; Kartheek, B. V. S. (International Journal of Research in Medical Sciences, 2016)
Background: Biliary brushing during endoscopic retrograde cholangiography pancreatography (ERCP) helps in the diagnosis of lesions of biliary tract. We compared the cellular and diagnostic results of various samples taken from the stricture site with the help of brushings taken from stricture site. The aim of this study was to know the age and sex prevalence in subjects suffering from biliary tract lesions and to know the role of ERCP guided brush cytology smears in diagnosing various lesions of exrtrahepatic biliary tract. Methods: It is a hospital based study conducted in the Department of Pathology, Andhra Medical College. Brush cytology smears were obtained from twenty patients and cytological examinations was conducted. All the clinical details and investigation reports were collected. Results: The age group of patients in this study ranged from 30 to 75 years. The numbers of cases analyzed during this period were 20. The mean age of presentation was 55 years. Male: Female ratio was 3:2. Majority of these cases presented with obstructive jaundice. Brush cytology smears from distal bile duct showed malignant cells hence our study revealed distal bile duct is more vulnerable to malignancy. Among all the 20 cases, 12 cases (60%) were reported as cholangiocarcinoma and the remaining 8 cases (40%) were included under benign/reactive. Among benign/reactive lesions, one case showed Micro-filarial infestation with reactive atypia of cells. Conclusions: The current study was conducted to assess the relative accuracy of brush cytology for diagnosis of malignant biliary strictures.